An analysis of students’ classroom interaction in English Language teaching and learning at MTs Terpadu Berkah Palangka Raya - Amanda, Maulidina Tri; Qalyubi, Imam; Qamariah, Zaitun (ARKA INSTITUTE, 2025)
This study examined classroom interaction in English Language Teaching and Learning at MTs Terpadu Berkah Palangka Raya through a qualitative case study. It aimed to identify the interaction patterns occurring during lessons and the factors that influenced interaction in improving students’ English skills. The subjects of this study were an English teacher and a class of eighth-grade students selected through purposive sampling. Data were collected through observation, semi-structured interviews, and documentation, then analyzed using the Flanders Interaction Analysis Category System (FIACS). The findings showed that teacher talk dominated the classroom, while student was relatively limited and silence/confusion appeared frequently. Student participation was mainly in the form of short responses, with very few initiations. Interviews revealed that psychological and linguistic barriers such as shyness, lack of confidence, and limited vocabulary combined with external influences including teacher-centered strategies, curriculum demands, and the cultural setting of madrasah, contributed to these interactional patterns. The results of the study conclude that interactions in English classes in this context remain teacher-centered, thereby limiting opportunities for students to develop their communicative skills. The study highlights the need for more student-centered approaches to enhance participations and support language development.